A new species and a key to known species of the genus Atractomorpha (Orthoptera, Acridoidea, Pyrgomorphidae) from China - Yin, Xiang-Chu; Shi, Jian-Ping (Zootaxa, 2007)
A new species, Atractomorpha taiwanensis sp. n. from Taiwan, China, is described in this paper. The new species is similar to A. micropenna Zheng, 1992, but it differs from the latter by the following: lateral lobe of pronotum without membranous area near posterior margin; the tegmina strongly shortened, not reaching (in male) the midpoint of hind femur; and wings very small, not reaching the midpoint of tegmina. A key to all known species of the genus Atractomorpha from China is given. The type specimens are deposited in the Museum of Hebei University, China.